Analysis of The Impact of Covid-19 on Non Performing Finance, Digital Banking and Fintech on The Profitability of Sharia and Conventional Banks With Macro Economy as Moderation - Synatrya, Ulin Nuha; Pramono, Nugroho Heri (Ekonomi Syariah IAIN Kudus, 2022)
This study was aimed to obtain empirical evidence regarding the influence of Non-performing Financing (NPL and NPF), Digital Banking (internet banking and mobile banking), and Fintech (peer to peer lending) on the profitability of Islamic Banks (Zakat) and Conventional Banks (ROA) with macroeconomic condition (GDP) as a moderating variable. The population in this study included Islamic Commercial Banks and Conventional Commercial Banks registered by Financial Services Authority (Otoritas Jasa Keuangan in Indonesian and it was abbreviated in English as FSA) and the sampling method was purposive sampling. The research data used were financial statements for the 2020 period with a total sample of 13 Islamic Commercial Banks and 45 Conventional Commercial Banks. The method of analysis was MRA which was processed by Eviews 11. The results showed that NPL and digital banking had an effect on the profitability (ROA) of conventional banks. Fintech had no effect on the profitability (ROA) of conventional banks. While the NPF affected the profitability (zakat) of Islamic banks. Digital banking had an effect on the profitability (zakat) of Islamic banks, and fin-tech had no effect on the profitability (zakat) of Islamic banks. Based on the MRA macroeconomic test (GDP it could moderate the effect of NPL on ROA and the effect of NPF on zakat. Meanwhile, macroeconomic (GDP) could not moderate the influence of Digital Banking and fin-tech on ROA and zakat.